Battery and pole piece structure thereof

By introducing a weakened transport layer and an active material layer into the electrode structure of the lithium-ion battery, the detachment of lithium ions at the edge of the electrode sheet is suppressed, the problem of lithium ions precipitation is solved, and the safety and performance uniformity of the battery are improved.

CN222785293UActive Publication Date: 2025-04-22HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420563032.1
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2025-04-22
Estimated Expiration
2034-03-22

AI Technical Summary

Technical Problem

Due to the inconsistent rates of lithium ions embedded and detachment of the electrode plate edges of existing lithium ion batteries, lithium ions are easily precipitated, causing lithium ions to be excreted at the edges of the electrode plate, affecting the performance and safety of the battery cell.

Method used

A battery electrode structure is adopted, including a metal layer, a weakened transport layer and an active material layer. The active material layer covers the surface of the weakened transport layer and the metal layer, weakening the weak conductivity of the transport layer, reducing the electron transmission rate, and inhibiting the detachment of lithium ions.

Benefits of technology

It effectively suppresses the discharge speed of lithium ions at the edge of the electrode plate, prevents lithium ion from being excreted at the edge of the electrode plate, and improves the charging and discharging safety and performance uniformity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222785293U_ABST
    Figure CN222785293U_ABST
Patent Text Reader

Abstract

The utility model belongs to the technical field of batteries, and particularly relates to a pole piece structure of a battery, which comprises a metal layer, the edge of the first end part of the metal layer is provided with a transmission weakening layer, one surface of the transmission weakening layer far away from the metal layer is provided with an active material layer, and the active material layer covers the surfaces of the transmission weakening layer and the metal layer. According to the utility model, the lithium ion separation speed at the edge part of the pole piece can be effectively inhibited, so that the problem of lithium separation at the head and tail parts of the pole piece is avoided. In addition, the utility model also discloses a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of batteries, and particularly relates to a battery and a pole piece structure thereof. Background Art

[0002] In the existing lithium-ion battery, the head and tail are close to the edge of the battery. When the battery kinetic window is insufficient or the interface between the cathode, anode and separator is affected by the manufacturing process, due to the edge effect of the battery, the lithium ion insertion and extraction rates at the edge of the battery core are inconsistent with those of the main part, resulting in lithium ions being easily precipitated at the edge of the pole piece, causing lithium precipitation at the edge of the pole piece of the battery core, and causing the head and tail of the battery core to be extra thick, then causing the performance failure and safety risk of the battery core. In the existing technology, there is no effective improvement measure for this abnormality. It can be seen that how to make the pole piece structure of the battery have sufficient safety has become an important difficulty in the battery structure design. For this reason, it is urgent to propose a new technical solution to solve the above problems. Summary of the Utility Model

[0003] One of the purposes of the utility model is to provide a pole piece structure of a battery, which can effectively inhibit the lithium ion extraction rate at the edge of the pole piece, thereby ensuring that there is no lithium precipitation problem at the head and tail of the pole piece.

[0004] To achieve the above purpose, the utility model adopts the following technical scheme:

[0005] A pole piece structure of a battery includes a metal layer. A weakened transmission layer is provided at the edge of the first end of the metal layer. An active material layer is provided on the surface of the weakened transmission layer away from the metal layer, and the active material layer covers the surfaces of the weakened transmission layer and the metal layer.

[0006] Wherein, the active material layer covering the surfaces of the weakened transmission layer and the metal layer can ensure that the area of the metal layer except the weakened transmission layer, that is, the main part of the metal layer, can quickly achieve ion transmission.

[0007] As an improvement of the pole piece structure of the battery of the utility model, the thickness value of the active material layer embedded in the weakened transmission layer is d um, and the thickness value of the weakened transmission layer is D1 um, satisfying the relationship: d < D1, so as to ensure that the slurry of the active material layer does not contact the metal layer.

[0008] As an improvement to the electrode structure of the battery of the present utility model, the active material layer has a first part and a second part connected to each other. The first part and the weakening transmission layer are stacked along the thickness direction of the electrode structure to form a first stacking area. The second part and the first stacking area are arranged side by side on the metal layer. The thickness difference between the second part and the first stacking area is H, that is, there is a thickness difference of H um between the second part and the first stacking area. H and D1 satisfy the relational expression: 0 ≤ H / D1 ≤ 3. Within the above range, the thickness uniformity of the electrode can be guaranteed, and the charge and discharge uniformity of the battery is improved.

[0009] As an improvement to the electrode structure of the battery of the present utility model, the thickness value of the active material layer embedded in the weakening transmission layer is d um. The active material layer has active particles with an average particle size of d2 um, and they satisfy the relational expression: 0.05 ≤ d / d2 ≤ 0.3. Among them, this numerical range can prevent the thickness of the active material layer embedded in the weakening transmission layer from being too large, so as to ensure that the active particles of the active material layer do not contact and scratch the metal layer. Moreover, it is also necessary to prevent the thickness of the active material layer embedded in the weakening transmission layer from being too small, so as to prevent the poor adhesion between the active material layer and the weakening transmission layer and cause easy film peeling.

[0010] As an improvement to the electrode structure of the battery of the present utility model, D1 and d2 satisfy the relational expression: 0.1 ≤ D1 / d2 ≤ 0.4. Within this thickness range, the effect of suppressing the lithium ion extraction speed at the edge part of the electrode is the best, effectively overcoming the safety problem of lithium deposition at the edge of the electrode and improving the charge and discharge safety of the battery.

[0011] As an improvement to the electrode structure of the battery of the present utility model, the weakening transmission layer has granular bodies with an average particle size of d1 um. d1, d, and D1 satisfy the relational expression: d < d1 < D1 or d1 < d < D1. Among them, the granular bodies can be ceramic particles. As weak conductive particles, ceramic particles have the effect of reducing electron transmission. The weakening transmission layer can be made by mixing a conductive agent and ceramic particles with an average particle size of d1 um.

[0012] As an improvement to the electrode structure of the battery of the present utility model, the width value of the weakening transmission layer is W1. W1 and D1 satisfy the relational expressions: 0.005 ≤ D1 / W1 ≤ 0.025, 0.025 ≤ D1 / W1 ≤ 0.05. Within this ratio range, the effect of suppressing the lithium ion extraction speed at the edge part of the electrode is the best, effectively overcoming the safety problem of lithium deposition at the edge of the electrode and improving the charge and discharge safety of the battery.

[0013] As an improvement to the electrode structure of the battery of the present utility model, the resistance value of the active material layer is R1, and the total resistance value of the metal layer, the weakening transmission layer and the active material layer is R2, satisfying the relational expression: 1.3 ≤ R2 / R1 ≤ 1.8.

[0014] As an improvement to the electrode structure of the battery of the present utility model, the conductivity of the weakening transmission layer is not greater than 50% of the conductivity of the active material layer, and the conductivity of the weakening transmission layer is not less than 0.5×10 -5 S / cm, so as to effectively regulate the performance of reducing electron transmission.

[0015] As an improvement to the electrode structure of the battery of the present utility model, the conductivity of the weakening transmission layer is σ1, the conductivity of the active material layer is σ2, and the thickness value of the active material layer located on the surface of the weakening transmission layer is L2 um, satisfying the relational expression: 100 ≤ (σ2 / σ1)×L2 ≤ 110, 0.05 ≤ σ1 / σ2 ≤ 0.5, d2 < L2, and σ2 is 1×10 -4 S / cm to 9×10 -2 S / cm. Within the above range, the effect of suppressing the lithium ion extraction speed at the edge part of the electrode can be guaranteed to be the best, effectively overcoming the safety problem of lithium deposition at the edge of the electrode and improving the charge and discharge safety of the battery.

[0016] As an improvement to the electrode structure of the battery of the present utility model, when the active material layer is in a liquid state, the contact angle with the surface of the solid weakening transmission layer is θ°, and θ, d, D1, R1 and R2 satisfy the relational expression: 2 ≤ (D1 - d)×θ×R2 / R1 ≤ 50. Within the above range, a better bonding effect between the active material layer and the weakening transmission layer and the appearance of the electrode can be guaranteed, improving the charge and discharge safety of the battery.

[0017] As an improvement to the electrode structure of the battery of the present utility model, the resistance value of at least part of the active material layer is 0.1Ω to 10Ω. Among them, this resistance value can be only the resistance value of the area where the active material layer covers the weakening transmission layer, or the resistance value of the overall area where the active material layer covers both the weakening transmission layer and the metal layer. Within this numerical range, the effect of suppressing the lithium ion extraction speed at the edge part of the electrode can be guaranteed to be the best.

[0018] As an improvement of the pole piece structure of the battery of the utility model, the d2 is 10-30, the d1 is 0.5-3, the d is 1-3, the D1 is 1-4, the θ is 0.1-20, and the H is 0-10. Within the above numerical ranges, the active material layer has active particles with an average particle size of 10um-30um, the thickness of the active material layer embedded in the weakened transport layer is 1um-3um, the weakened transport layer has particles with an average particle size of 0.5um-3um, the thickness of the weakened transport layer is 1um-4um, and when the active material layer is in liquid state, it forms a contact angle with the surface of the weakened transport layer in a solid state with a value of 0.1°-20°. The thickness difference between the second part and the first overlapping area is 0um-10um, which can ensure that the lithium ion escape speed is best suppressed at the edge of the pole piece, effectively overcome the safety problem of lithium deposition at the edge of the pole piece, and at the same time ensure the uniformity of the pole piece, thereby improving the charging and discharging safety of the battery.

[0019] The second purpose of the utility model is to provide a battery, comprising the above-mentioned pole piece structure.

[0020] The beneficial effect of the utility model is that: the pole piece structure of the battery of the utility model includes a metal layer, the edge of the first end of the metal layer has a weakened transmission layer, the side of the weakened transmission layer away from the metal layer has an active material layer, the active material layer covers the surface of the weakened transmission layer and the metal layer, the weak conductivity of the weakened transmission layer can reduce the transmission rate of electrons and inhibit the release speed of lithium ions at the edge of the pole piece, which can effectively solve the safety problem of lithium deposition at the edge of the pole piece and ensure that lithium deposition will not occur at the head and tail of the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is one of the structural schematic diagrams of the metal layer, the transmission weakening layer and the active material layer of the utility model.

[0022] Figure 2 This is the second structural schematic diagram of the metal layer, the transmission weakening layer and the active material layer of the utility model.

[0023] Figure 3 It is a schematic diagram of the structure of the pole piece of the utility model.

[0024] Figure 4 It is a schematic diagram of reducing the ion transmission difference between the transport layer and the active material layer of the present invention.

[0025] Among them: 1, metal layer; 2, weakened transmission layer; 21, particle body; 3, active material layer; 3a, first part; 3b, second part; 31, active particles; D1, thickness value of weakened transmission layer; d, thickness value of active material layer embedded in weakened transmission layer; H, thickness difference between the second part of active material layer and the first overlapping area formed in pole piece structure; T, thickness direction of pole piece structure. DETAILED DESCRIPTION

[0026] If certain words are used in the specification and claims to refer to specific components, those skilled in the art should understand that manufacturers may use different terms to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but rather use differences in components' functions as the criteria for distinction. For example, "including" mentioned throughout the specification and claims is an open term and should be interpreted as "including but not limited to".

[0027] The following is combined with Figures 1 to 4 The utility model is further described in detail with specific embodiments, but is not intended to limit the utility model.

[0028] A battery electrode structure, see Figures 1 to 3 , including a metal layer 1, a first end edge of the metal layer 1 having a weakened transmission layer 2, a side of the weakened transmission layer 2 away from the metal layer 1 having an active material layer 3, the resistance value of the active material layer 3 is R1, and the total resistance value of the metal layer 1, the weakened transmission layer 2 and the active material layer 3 is R2, satisfying the relationship: 1.3≤R2 / R1≤1.8, more preferably, satisfying the relationship: 1.5≤R2 / R1≤1.7.

[0029] Preferably, the active material layer 3 covers the surfaces of the weakened transport layer 2 and the metal layer 1, and the resistance value of at least part of the active material layer 3 is 0.1Ω~10Ω, wherein the resistance value can be only the resistance value R1 of the area where the active material layer 3 covers the weakened transport layer 2, or it can be the resistance value of the entire area where the active material layer 3 covers both the weakened transport layer 2 and the metal layer 1.

[0030] Preferably, the thickness of the active material layer 3 embedded in the weakened transmission layer 2 is d um, and the active material layer 3 has active particles 31 with an average particle size of d2 um, satisfying the relationship: 0.05≤d / d2≤0.1, 0.1≤d / d2≤0.15, 0.15≤d / d2≤0.2, 0.2≤d / d2≤0.25 or 0.25≤d / d2≤0.3.

[0031] Preferably, the thickness value of the attenuation transmission layer 2 is D1 um, and D1, d, and d2 satisfy the relational expression: d < D1, 0.1 ≤ D1 / d2 ≤ 0.4. Among them, D1 and d2 satisfy the relational expression: 0.1 ≤ D1 / d2 ≤ 0.15, 0.15 ≤ D1 / d2 ≤ 0.17, 0.17 ≤ D1 / d2 ≤ 0.195, 0.195 ≤ D1 / d2 ≤ 0.25, 0.25 ≤ D1 / d2 ≤ 0.3, 0.3 ≤ D1 / d2 ≤ 0.35, or 0.35 ≤ D1 / d2 ≤ 0.4.

[0032] Preferably, the attenuation transmission layer 2 has particulate bodies 21 with an average particle size of d1 um, and d1, d, and D1 satisfy the relational expression: d < d1 < D1 or d1 < d < D1.

[0033] Preferably, the width value of the attenuation transmission layer 2 is W1, and W1 and D1 satisfy the relational expression: 0.005 ≤ D1 / W1 ≤ 0.015, 0.015 ≤ D1 / W1 ≤ 0.025, 0.025 ≤ D1 / W1 ≤ 0.03, 0.03 ≤ D1 / W1 ≤ 0.035, 0.035 ≤ D1 / W1 ≤ 0.04, 0.04 ≤ D1 / W1 ≤ 0.045, or 0.045 ≤ D1 / W1 ≤ 0.05.

[0034] Preferably, the conductivity of the attenuation transmission layer 2 is not greater than 50% of the conductivity of the active material layer 3, and the conductivity of the attenuation transmission layer 2 is not less than 0.5×10 -5 S / cm.

[0035] Preferably, the conductivity of the attenuation transmission layer 2 is σ1, the conductivity of the active material layer 3 is σ2, and the thickness value of the active material layer 3 located on the surface of the attenuation transmission layer 2 is L2 um, satisfying the relational expression: 100 ≤ (σ2 / σ1)×L2 ≤ 110, 0.05 ≤ σ1 / σ2 ≤ 0.5, d2 < L2, and σ2 is 1×10 -4 S / cm to 9×10 -2 S / cm.

[0036] Preferably, when the active material layer 3 is in a liquid state, it forms a contact angle of θ° with the surface of the solid attenuation transmission layer 2, that is, the slurry of the active material layer 3 drops onto the surface of the attenuation transmission layer 2 to form a contact angle with a degree value of θ°. This contact angle is formed by the contact of the liquid and solid before drying. Actually, it is the interfacial angle formed when the active material layer 3 is in a liquid state and the attenuation transmission layer 2 is in a solid state. The solid content of the liquid active material layer 3 is 45 - 55%; the weight loss rate of the solid attenuation transmission layer 2 is ≤1%.

[0037] More preferably, the value of the contact angle θ, the thickness d of the active material layer 3 embedded in the weakened transport layer 2, the thickness D1 of the weakened transport layer 2, the resistance R1 of the active material layer 3 and the metal layer 1, and the total resistance R2 of the weakened transport layer 2 and the active material layer 3 satisfy the relationship: 2≤(D1-d)×θ×R2 / R1≤15, 15≤(D1-d)×θ×R2 / R1≤30, 30≤(D1-d)×θ×R2 / R1≤50, wherein the value of the contact angle can be 0.1°~20°.

[0038] Preferably, the active material layer 3 has a first part 3a and a second part 3b connected to each other, the first part 3a and the weakened transmission layer 2 are overlapped along the thickness direction T of the pole piece structure to form a first overlapping area, the second part 3b and the first overlapping area are arranged in parallel on the metal layer 1, and the thickness difference between the second part 3b of the active material layer 3 and the first overlapping area formed in the pole piece structure is H, and H and the thickness value D1 of the weakened transmission layer 2 satisfy the relationship: 0≤H / D1≤1, 1≤H / D1≤2, 2≤H / D1≤3, and H is the thickness difference between the first overlapping area and the second part 3b on a single side of the pole piece.

[0039] Preferably, the metal layer 1 has two opposite first end edges, the two transmission weakening layers 2 are relatively arranged on the same side of the metal layer 1, and there are four transmission weakening layers 2 on the front and back sides of the metal layer 1. Among them, R2 can be the total resistance value of the entire system composed of the metal layer 1, the four transmission weakening layers 2 on the front and back sides of the metal layer 1, and the two active material layers 3 on the front and back sides of the metal layer 1.

[0040] The resistance value test method adopts the four-wire two-probe test principle, and the selected test area can be 154.025mm 2 The starting recording pressure can be 0.35-0.45T, and the time interval can be 1s. The contact angle test method is the sessile drop method, and the test is completed using an optical contact angle meter.

[0041] In addition, the utility model also provides a battery, including a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet of the battery is the above-mentioned electrode sheet structure containing a metal layer 1, a weakened transmission layer 2 and an active material layer 3, wherein the battery can be a lithium ion battery, a sodium ion battery, a magnesium ion battery, etc.

[0042] Example 1

[0043] Positive electrode: see Figures 1 to 3, comprising a metal layer 1, a weakened transmission layer 2 and an active material layer 3, wherein the metal layer 1 is an aluminum current collector, and a weakly conductive material is first coated on the aluminum current collector, and the weakly conductive material can be prepared by mixing a conductive agent and ceramic particles with an average particle size of d1, wherein d1 is 1.5um, and the weakly conductive material is coated at a position corresponding to the head and tail of the battery cell, that is, the weakened transmission layer 2 is coated on the edge of the first end of the metal layer 1 to obtain a weakly conductive current collector, and then the positive electrode active material, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully and uniformly dispersed in an N-methylpyrrolidone solvent system in a weight ratio of 97.8:0.6:0.4:1.2 to obtain a positive electrode active material slurry, and the positive electrode active material slurry is the active material layer 3, wherein the positive electrode active material can be LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5 O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2 or more, the active particles 31 are a mixture of positive electrode active material, conductive agent acetylene black, and conductive carbon nanotubes, and finally the positive electrode active material slurry is coated on the weakly conductive current collector, the part of the positive electrode active material slurry superimposed on the weakened transmission layer 2 is the first part 3a, and the part of the positive electrode active material slurry not superimposed on the weakened transmission layer 2 is the second part 3b, and then cold pressed and divided into strips to obtain the positive electrode sheet.

[0044] Negative electrode sheet: negative electrode active material, sodium carboxymethyl cellulose and styrene-butadiene rubber (SBR) emulsion are mixed in a weight ratio of 97.4:1.3:1.3 to prepare negative electrode active material slurry. The negative electrode active material can be a silicon-carbon material; the active material slurry is coated on a copper current collector to obtain an active material layer, and then cold pressed and striped to obtain a negative electrode sheet.

[0045] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.

[0046] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0047] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0048] Among them, the resistance value R1 of the active material layer 3 in the positive electrode sheet is 2Ω, the total resistance value R2 of the metal layer 1, the weakened transmission layer 2 and the active material layer 3 is 3Ω, the thickness d of the first part 3a of the active material layer 3 embedded in the weakened transmission layer 2 is 2.4um, the thickness D1 of the weakened transmission layer 2 is 3.7um, the average particle size d2 of the active particles 31 is 19um, and the conductivity σ1 of the weakened transmission layer 2 is 4.6×10 -3 S / cm, and the conductivity σ2 of the active material layer 3 is 1×10 -2 S / cm, the thickness L2 of the active material layer 3 located on the surface of the weakened transmission layer 2 is 50um, and the first overlapping area formed by the overlapping of the weakened transmission layer 2 and the first part 3a of the active material layer 3 in the electrode structure and the second part 3b of the adjacent active material layer 3 form a thickness difference H of 4.6um. The slurry of the active material layer 3 is dripped onto the surface of the weakened transmission layer 2 to form a contact angle of θ°=5°, and by adjusting R1, R2, d, D1 and d2, the following embodiments 2 to 4 and comparative examples 1 to 4 are obtained, and the specific parameters are shown in Table 1.

[0049] Moreover, H, θ, L2, σ1 and σ2 in Examples 1 to 4 and Comparative Examples 1, 2 and 4 are all the same; R1, d and d2 in Example 1 and Example 2 are all the same, and only R2 and D1 are different; R2 and d2 in Example 1 and Comparative Example 1 are all the same, and only R1, d and D1 are different; d, D1 and d2 in Example 1 and Comparative Example 4 are all the same, and only R1 and R2 are different; R1, R2, D1 and d2 in Example 3 and Example 4 are all the same, and only d is different; R2, D1 and d2 in Example 3 and Comparative Example 2 are all the same, and only R1 and d are different; L2, σ2, R1 and d2 in Example 3 and Comparative Example 3 are all the same, and H, θ, σ1, d and D1 in Comparative Example 3 are all 0.

[0050]

[0051]

[0052] Table 1

[0053] Performance tests were conducted on Examples 1 to 4 and Comparative Examples 1 to 4, and the charging window is the maximum rate at which the battery cell does not deposit lithium after the battery cell interface is disassembled at the cut-off voltage when the battery cell is directly charged under the conditions of 5.0C, 5.2C, 5.4C, 5.6C, 5.8C, and 6.0C.

[0054] The lithium precipitation windows of Examples 1 to 4 and Comparative Examples 1 to 4 were tested and shown in Table 2 below.

[0055] Lithium Separation Window Example 1 6C Example 2 5.8C Example 3 5.8C Example 4 5.8C Comparative Example 1 5.4C Comparative Example 2 5.2C Comparative Example 3 5.0C Comparative Example 4 5.2C

[0056] Table 2

[0057] When there is no weakly conductive layer or when the particles of the active material layer pierce the weakly conductive layer and directly contact the foil, the electron transmission rate cannot be effectively suppressed, resulting in an accelerated rate of lithium ion escape, resulting in lithium precipitation.

[0058] See also Figure 4 , weakening the transport layer 2 effectively reduces the electron transmission rate and inhibits the escape rate of lithium ions.

[0059] Therefore, one of the keys of this solution is to control the resistance ratio of the electrode film with or without a weak conductive layer, the thickness of the active material layer embedded in the weak conductive coating, and the relationship between the thickness of the weak conductive coating and the average particle size of the active material layer, that is, to control the resistance value R1 of the active material layer 3 in the positive electrode, the total resistance value R2 of the metal layer 1, the weakened transmission layer 2 and the active material layer 3, the thickness d of the active material layer 3 embedded in the weakened transmission layer 2, the thickness D1 of the weakened transmission layer 2 and the average particle size d2 of the active particles 31, so that 1.3R1 ≤R2≤1.8R1, 0.05d2≤d≤0.3d2, 0.1d2≤D1≤0.4d2 and d<D1; d is 1um~3um; D1 is 1um~4um; d2 is 10um~30um; R1 is 0.1Ω~10Ω; Under these conditions, the weakly conductive coating reduces the transmission rate of electrons, inhibits the escape rate of lithium ions, and ensures that the particles of the active material layer will not pierce the weakly conductive layer, so as not to directly contact the foil and cause the effect of reducing the transmission rate of electrons to fail.

[0060] In addition, by only changing the value of L2 on the basis of Example 1 to obtain Example 5, and by only changing L2, σ1 and σ2 on the basis of Example 5 to obtain Examples 6-7 and Comparative Examples 5-8, the influence of such a pole piece structure on the charging time is demonstrated, that is, the relationship between the conductivity of the weakened transmission layer 2 being σ1, the conductivity of the active material layer 3 being σ2, and the thickness of the active material layer 3 located on the surface of the weakened transmission layer 2 being L2 is further explored to obtain the design parameters of Table 3 and the corresponding time of full charge under the conditions of 2C and 4C cycle standards in Table 4 is obtained based on such parameters. At the same time, such a test can meet the single variable principle, and Examples 6-7 and Comparative Examples 5-8 and

[0061] Compared with Example 1 in Table 1, the variables are only L2, σ1 and σ2.

[0062]

[0063]

[0064] Table 3

[0065] The charging window is the maximum rate at which the battery cell can be directly charged to the cut-off voltage under the conditions of 2.0C, 2.5C, 3.0C, 3.5C, 4.0C, and 4.5C without lithium plating on the cell interface after disassembly. The charging time is the time corresponding to a full charge under the conditions of 2C and 4C cycling modes. By comparing Examples 5-7 with Comparative Examples 5-8, the following results are obtained.

[0066] Lithium Separation Window 2C charging time 4C charging time Example 5 4.5C 34min 24min Example 6 4.5C 39min 26min Example 7 4.5C 38min 25min Comparative Example 5 3.5C 30min 21min Comparative Example 6 4.0C 49min 35min Comparative Example 7 2.0C 40min 23min Comparative Example 8 2.5C 54min 37min

[0067] Table 4

[0068] It can be seen from the table that when the conductivity of the weak conductive coating does not match the conductivity of the active material layer and the thickness of the electrode sheet, it significantly affects the performance of the battery cell. When (σ2 / σ1)×L2<100, the lithium ion insertion / extraction rate is too slow and the charging time increases. When (σ2 / σ1)×L2>110, the electron transfer rate cannot be effectively inhibited, resulting in an accelerated lithium ion extraction rate and lithium plating phenomenon. It can be seen that by weakening the conductivity of the transport layer 2 to σ1, the conductivity of the active material layer 3 to σ2, and the thickness of the active material layer 3 on the surface of the weakened transport layer 2 to L2, satisfying the relationship: 100≤(σ2 / σ1)×L2≤110, 0.05≤σ1 / σ2≤0.5, d2<L2, and σ2 being 1×10 -4 S / cm~9×10 -2 S / cm, within the above range, the lithium ion extraction speed can be effectively inhibited at the edge of the electrode sheet, effectively overcoming the safety problem of lithium plating at the edge of the electrode sheet and improving the charge and discharge safety of the battery.

[0069] On the other hand, in this solution, Examples 8-11 are obtained by only changing the value of θ based on Examples 1-4, and Comparative Examples 9-12 are obtained by only changing θ based on Comparative Examples 1-4. Comparative Example 13 is obtained by only changing the value of θ based on Example 8, Comparative Example 14 is obtained by only changing the value of D1 based on Example 8, and Comparative Example 15 is obtained by only changing the value of d based on Example 8. To explore the relationship between the angle value θ of the contact angle formed when the slurry of the active material layer 3 drops onto the surface of the weakened transport layer 2, the resistance value R1 of the active material layer 3 in the positive electrode sheet, the total resistance value R2 of the metal layer 1, the weakened transport layer 2, and the active material layer 3, the thickness value d of the active material layer 3 embedded in the weakened transport layer 2, and the thickness value D1 of the weakened transport layer 2, the design parameters in Table 5 and

[0070] the difference in Poweloss under the 2C cycling mode condition in Table 6 are obtained.

[0071] <![CDATA[R1(Ω)]]> <![CDATA[R2(Ω)]]> d(um) <![CDATA[D1(um)]]> <![CDATA[θ( 0 )]]> Example 8 2 3 2.4 3.7 3 Example 9 2 3.4 2.4 3.4 20 Example 10 0.7 1.0 1.3 2.9 10 Embodiment 11 0.7 1.0 2.4 2.9 20 Comparative Example 9 1.9 3 3.7 3.4 15 Comparative Example 10 0.8 1.0 3.6 2.9 20 Comparative Example 11 0.7 0.7 0 0 180 Comparative Example 12 1.2 2.4 2.4 3.7 60 Comparative Example 13 2 3 2.4 3.7 27 Comparative Example 14 2 3 2.4 1.4 3 Comparative Example 15 2 3 3.6 3.7 3

[0072] Table 5

[0073] Powerloss refers to the difference between the capacity ratio of standard charge and discharge per 100-cycle node and the capacity ratio of standard charge and discharge at the adjacent cycle number cycle, which is used to characterize the polarization of the battery cell. The larger the powerloss, the greater the polarization of the battery cell, and vice versa. By comparing Examples 8 to 11 and Comparative Examples 9 to 15, the results in Table 6 are obtained.

[0074]

[0075] Table 6

[0076] It can be seen from the table that when the electrode film resistance ratio with or without a weak conductive layer, the thickness of the active material layer 3 embedded in the weak conductive coating, and the contact angle with a value of θ° formed by the slurry of the active material layer 3 dripping onto the surface of the weakened transmission layer 2 show an unmatched relationship, that is, (D1-d)×θ×R2 / R1 is too large or too small, it will obviously affect the performance of the battery cell. When 2≤(D1-d)×θ×R2 / R1≤50, there is a better bonding effect and electrode appearance between the active material layer 3 and the weakened transmission layer 2. As the cycle proceeds, the electrode is in a stable state and the polarization grows slowly. When 50<(D1-d)×θ×R2 / R1 or (D1-d)×θ×R2 / R1<2, the bonding effect between the active material layer 3 and the weakened transmission layer 2 is weak. As the cycle proceeds, the active material layer 3 and the weakened transmission layer 2 begin to separate, resulting in a significant increase in the polarization of the battery cell, affecting the cycle performance of the battery cell.

[0077] Finally, this solution also demonstrates the influence of such a pole piece structure on the uniformity of charge and discharge by only changing the value of H on the basis of Example 1 to obtain Example 12, and by only changing H and D1 on the basis of Example 12 to obtain Examples 13-14 and Comparative Examples 16-18, that is, further exploring the relationship between H and the thickness value D1 of the weakened transmission layer 2 to obtain the design parameters of Table 7 and the difference in capacity retention under the 5C cycle standard conditions of Table 8 according to such parameters. At the same time, such a test can meet the single variable principle. Compared with Example 1 in Table 1, the variables of Examples 13-14 and Comparative Examples 16-18 are only H and D1.

[0078] <![CDATA[D1(um)]]> H(um) Example 12 3.7 3 Embodiment 13 3.4 5 Embodiment 14 2.9 7 Comparative Example 16 3.7 13 Comparative Example 17 3.4 11 Comparative Example 18 2.9 14

[0079] Table 7

[0080] The following results were obtained by comparing Examples 12 to 14 with Comparative Examples 16 to 18.

[0081]

[0082] Table 8

[0083] It can be seen from the table that when H does not match the thickness value D1 of the weakened transmission layer 2, the performance of the battery cell is significantly affected. When 3≤H / D1, the thickness uniformity of the pole piece is poor, and there is local polarization inconsistency, resulting in poor charge and discharge uniformity, thereby affecting the cycle retention rate. It can be seen that when H and the thickness value D1 of the weakened transmission layer 2 satisfy the relationship: 0≤H / D1≤3, within the above range, the charge and discharge uniformity of the pole piece can be guaranteed, thereby improving the corresponding electrical performance.

[0084] According to the disclosure and teaching of the above description, those skilled in the art to which the utility model belongs can also change and modify the above implementation. Therefore, the utility model is not limited to the above specific implementation, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the utility model belongs to the protection scope of the utility model. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the utility model.

Claims

1. A battery pole piece structure, characterized in that: Comprising: A metal layer (1), the first end edge of the metal layer (1) having a weakened transmission layer (2); On the side of the weakened transmission layer (2) away from the metal layer (1) there is an active material layer (3); The active material layer (3) covers the surfaces of the weakened transmission layer (2) and the metal layer (1).

2. The battery pole piece structure according to claim 1, characterized in that: The thickness value of the active material layer (3) embedded in the weakened transmission layer (2) is d um, and the thickness value of the weakened transmission layer (2) is D1 um, satisfying the relationship: d < D1.

3. The battery pole piece structure according to claim 2, characterized in that: The active material layer (3) has a first part (3a) and a second part (3b) connected to each other. The first part (3a) and the weakened transmission layer (2) are superposed in the thickness direction of the electrode structure to form a first superposition region. The second part (3b) is arranged side by side with the first superposition region on the metal layer (1). The thickness difference between the second part (3b) and the first superposition region is H, and the H and the D1 satisfy the relationship: 0 ≤ H / D1 ≤ 3.

4. The pole piece structure of a battery as claimed in claim 2 or 3, characterized in that: The active material layer (3) has active particles (31) with an average particle size of d2 um, satisfying the relationships: 0.05 ≤ d / d2 ≤ 0.3, 0.1 ≤ D1 / d2 ≤ 0.

4.

5. The battery pole piece structure according to claim 2 or 3, characterized in that: The weakened transmission layer (2) has particulate bodies (21) with an average particle size of d1 um, and the d1, the d, and the D1 satisfy the relationship: d < d1 < D1 or d1 < d < D1.

6. The battery pole piece structure according to claim 2 or 3, characterized in that: The resistance value of the active material layer (3) is R1, and the total resistance value of the metal layer (1), the weakened transmission layer (2), and the active material layer (3) is R2, satisfying the relationship: 1.3 ≤ R2 / R1 ≤ 1.

8.

7. The battery pole piece structure according to claim 6, characterized in that: When the active material layer (3) is in a liquid state, the contact angle with the surface of the solid weakened transmission layer (2) is θ°. The θ, the d, the D1, the R1, and the R2 satisfy the relationship: 2 ≤ (D1 - d) × θ × R2 / R1 ≤ 50.

8. The battery pole piece structure according to any one of claims 1 to 3, characterized in that: The conductivity of the weakened transmission layer (2) is not greater than 50% of the conductivity of the active material layer (3), and the conductivity of the weakened transmission layer (2) is not less than 0.5×10 -5 S / cm.

9. The battery pole piece structure according to claim 8, characterized in that: The conductivity of the weakened transmission layer (2) is σ1, the conductivity of the active material layer (3) is σ2, and the thickness value of the active material layer (3) on the surface of the weakened transmission layer (2) is L2 um, satisfying the relationship: 100 ≤ (σ2 / σ1) × L2 ≤ 110, 0.05 ≤ σ1 / σ2 ≤ 0.

5.

10. The battery pole piece structure according to any one of claims 1 to 3, characterized in that: The width value of the weakened transmission layer (2) is W1, and the thickness value of the weakened transmission layer (2) is D1, satisfying the relationship: 0.005 ≤ D1 / W1 ≤ 0.

05.

11. A battery, characterized in that: Including the electrode structure according to any one of claims 1 to 10.